TGF-β: the connecting link between nephropathy and fibrosis. (2nd January 2016) - Sutariya, Brijesh; Jhonsa, Dimple; Saraf, Madhusudan N.
Abstract: Renal fibrosis is the usual outcome of an excessive accumulation of extracellular matrix (ECM) that frequently occurs in membranous and diabetic nephropathy. The result of renal fibrosis would be end-stage renal failure, which requires costly dialysis or kidney transplantation. Renal fibrosis typically results from chronic inflammation via production of several molecules, such as growth factors, angiogenic factors, fibrogenic cytokines, and proteinase. All of these factors can stimulate excessive accumulation of ECM components through epithelial to mesenchymal transition (EMT), which results in renal fibrosis. Among these, transforming growth factor-beta (TGF-β) is proposed to be the major regulator in inducing EMT. Besides ECM protein synthesis, TGF-β is involved in hypertrophy, proliferation, and apoptosis in renal cells. In particular, TGF-β is likely to be most potent and ubiquitous profibrotic factor acting through several intracellular signaling pathways including protein kinases and transcription factors. Factors that regulate TGF-β expression in renal cell include hyperglycemia, angiotensin II, advance glycation end products, complement activation (C5b-9), and oxidative stress. Over the past several years, the common understanding of the pathogenic factors that lead to renal fibrosis in nephropathy has improved considerably. This review will discuss the recent findings on the mechanisms and role of TGF-β in membranous and diabetic nephropathy.